(untitled) (Comparative Professional Pedagogy, 2021)
Features of non-formal and formal education are analyzed in the article. The specificity of formal education lies in the longevity of goals, academic content, the implementation of external quality control of education, structure, standardization, resource consumption, the availability of a document on education. Non-formal education is based on the integration of learning and life. It covers learning activities for people of all ages (children, adults, the elderly, whether girls, boys, women or men), in any living environment (family, school, community, workplace, etc.), and through various forms that together meet a wide range of educational needs. The author draws attention to the validation of non-formal education in foreign countries and gives examples of legal support for this process in countries such as the United Kingdom (official recognition of non-formal education by the Department of Business, Innovation and Qualifications in 2009), France (Law on Social Modernization (2002) and the introduction of French legislation on the concept of validation of knowledge gained through experience (Validation des Aquis de l’Expérience), Finland (the system of validation of non-formal and informal education is supported by the state, the process of validation is improved and standardized), the Netherlands (Education Professions Act (2004) and EVC – Erkenning Verworven Competenties evaluation procedure), Germany (two research projects: Weiterbildungspass (Continuing Education Passport) and Lernkultur Kompetenzentwicklung (Development of Competences as a Learning Culture). The author concludes that today the opposition of formal and non-formal education is considered unproductive. Actions based on the complementarity of different types of education are considered appropriate.